Aplicação Android com Firebase para administrar o uso de medicações - Ueda, Daniel Yudi (2020)
Medicines are used in the prevention, diagnosis, treatment of diseases and also in the control of symptoms, such as pain, for example. These drugs are purchased at pharmacies with a prescription or self-medication. An intake of medications should be performed in specific time, such as in hours, daily or weekly for example, or even in a single dose, depending on its use. The administration of these medications is very important for the expected result and can be satisfactory and can occur in different places, such as at home, at work place or even when the person is at leisure. A solution proposed through the development of this work is for Android mobile devices. The developed application allows the user to register and consult the medications he uses and which has already been determined its use in specific times. For the development of the system, Java technology and Firebase database were used.